Comparing The Impact Of An Astronomy Course And A Science And Society Seminar On Undergraduate Students’ Attitudes Toward Science (Journal of Astronomy & Earth Sciences Education, 2017)
A common challenge among university professors is how to best design undergraduate courses to successfully enhance students' attitudes. To compare which curriculum was more efficient at fostering a positive attitude towards science in general, I studied the impact of two different general education science courses on the attitudes of college students. The first course was an arithmetic-based Introductory Astronomy course for non-science majoring undergraduates that used interactive and inquiry-based teaching techniques. The comparison course was a Science, Technology, & Society (STS) seminar with context-based science contents, discussions, and intensive reading and writing. The postsemester results showed that neither curriculum on its own significantly changed the overall attitude of students towards science as far the assessment could measure, but that each curriculum did successfully enhance specific aspects of the students’ attitude in differing categories. The STS students had scores showing a gain in believing that scientists are honest. The astronomy students had scores showing a gain in understanding that scientific theories can change in the light of new evidence. However, the most significant change was a loss in the astronomy students’ confidence that the general public can and should understand science. Thus, the results suggest that professors who strongly desire to enhance the broad nature of students' attitudes need to use more purposeful instructional experiences rather than rely only on students' deepening understanding of the specific scientific content.
Keywords: Astronomy Education; Affect and Attitudes